2023
DOI: 10.1007/s42330-023-00263-4
|View full text |Cite
|
Sign up to set email alerts
|

Investigative Research Projects for Students in Science: The State of the Field and a Research Agenda

Abstract: One of the ways in which students can be taught science is by doing science, the intention being to help students understand the nature, processes, and methods of science. Investigative research projects may be used in an attempt to reflect some aspects of science more authentically than other teaching and learning approaches, such as confirmatory practical activities and teacher demonstrations. In this article, we are interested in the affordances of investigative research projects where students, either indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 83 publications
0
8
0
Order By: Relevance
“…It has been reported that project-based (sometimes interchanged with problem-based) learning (PBL) helps students in understanding the fundamentals of science while also developing transferable skills, such as problem solving and science communication . A specific type of PBL is an investigative research project (IRP), which is a student-led, open-ended research investigation frequently supported by a teacher and university or industry researcher . The Greener Fragrances project is best defined as an IRP closely allied with the better known PBL.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been reported that project-based (sometimes interchanged with problem-based) learning (PBL) helps students in understanding the fundamentals of science while also developing transferable skills, such as problem solving and science communication . A specific type of PBL is an investigative research project (IRP), which is a student-led, open-ended research investigation frequently supported by a teacher and university or industry researcher . The Greener Fragrances project is best defined as an IRP closely allied with the better known PBL.…”
Section: Introductionmentioning
confidence: 99%
“…Activities developed in partnership with universities or industry that provide younger students with opportunity to undertake research investigations over a period of time have been emerging in recent years. ,, While relatively new educational interventions, there is growing evidence that these longer-term STEM interventions have a more significant impact upon young people’s interests and aspirations than the traditional one-off activities frequently delivered in schools by industry and/or academic partners …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations